2013
DOI: 10.1007/s11695-012-0819-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ultrasound-Guided Transversus Abdominis Plane Block After Laparoscopic Bariatric Surgery: a Double Blind, Randomized, Controlled Study

Abstract: Our study demonstrates that the USG-TAP as part of multimodal analgesic technique in morbidly obese patients undergoing laparoscopic gastric bypass reduces opioid requirement, improves pain score, decreases sedation, promotes early ambulation, and has greater patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 25 publications
0
69
0
5
Order By: Relevance
“…33,37,63 All were laparoscopic procedures (single-port sleeve gastrectomy and gastric bypass surgery) studying the efficacy of TAP block compared with placebo. Transversus abdominal plane block reduced the six-hour pain score by 0.9 (95% CI, -1.3 to -0.5; P \ 0.001) and the 12-hr pain score by 1.1 (95% CI, -1.6 to -0.6; P \ 0.001).…”
Section: Transversus Abdominal Plane Block In Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…33,37,63 All were laparoscopic procedures (single-port sleeve gastrectomy and gastric bypass surgery) studying the efficacy of TAP block compared with placebo. Transversus abdominal plane block reduced the six-hour pain score by 0.9 (95% CI, -1.3 to -0.5; P \ 0.001) and the 12-hr pain score by 1.1 (95% CI, -1.6 to -0.6; P \ 0.001).…”
Section: Transversus Abdominal Plane Block In Bariatric Surgerymentioning
confidence: 99%
“…Transversus abdominal plane block reduced the six-hour pain score by 0.9 (95% CI, -1.3 to -0.5; P \ 0.001) and the 12-hr pain score by 1.1 (95% CI, -1.6 to -0.6; P \ 0.001). 33,37 All trials evaluated 24-hr pain scores and 24-hr morphine consumption. Transversus abdominal plane block did not reduce the 24-hr pain score (-0.6; 95% CI, -2.1 to 1.0; P = 0.48).…”
Section: Transversus Abdominal Plane Block In Bariatric Surgerymentioning
confidence: 99%
“…Sinha et al [11] demonstrated improvement of three different variables: lower pain scores in VAS, less need for opioids (Tramadol) therefore allowing for less sedation and early ambulation. Patient satisfaction scores were also significantly higher [11].…”
Section: Transverses Abdominis Plane Block (Tap) Blockmentioning
confidence: 99%
“…Bilateral TAP blocks were associated with significantly less morphine consumption however, no difference in pain scores. Another study looked at the benefit of TAP blocks in laparoscopic bariatric surgery and found lower pain scores and decreased analgesic requirements in the TAP block group [35].…”
Section: Laparoscopic Surgerymentioning
confidence: 99%